The Effect of Taxpayer Awareness and Tax Knowledge on Tax Compliance in Nepal - Bhattarai, Toya Nath; Khadka, Ajaya Kumar; Joshi, Ramesh Datta (NCC Journal, 2025)
This research paper examines the impact of taxpayer knowledge and awareness on tax compliance within the framework of Nepal's changing taxation system. A total of 384 taxpayers registered in Kathmandu Valley were selected for the study, which utilized a descriptive and explanatory methodology. The researcher gathered data using a structured questionnaire and analyzed it using linear regression. The results show that an individual's tax knowledge (r=0.482, p